Comparison of quartz vials with polypropylene vials for rapid cryopreservation of human ovarian tissue. Issue 1 (December 2016) - Scheiner, D.; Bracone, G.; Imesch, P.; Fink, D.; Hehl, J.; Imthurn, B.
Abstract Background Because higher survival of follicles during the freezing/thawing procedure improves the quality of cryopreserved tissue reimplanted after oncological therapies, defining an optimal method for human ovarian tissue cryopreservation remains a major issue in this field. One option to improve the cryopreservation procedure is to use better materials, i.e., vials with better conductivity. The aim of this study was to compare polypropylene (PP) with quartz vials. Between September 2012 and January 2013, eight patients were recruited. The ovarian cortex was cut into 3 slices, assigned randomly to a fresh and a cryopreserved group in PP (method B) or quartz vials (method C). Histological and immunohistochemical (IHC) analysis were used. For IHC three antibodies were analyzed: Ki67 (proliferation index), Bcl2 (anti apoptotic index) and Hsp70 (stress index). Results The majority of GCs showed positive staining for Bcl2 in both cryopreservation device, with higher expression in group C than in group B. Oocytes and their nuclei showed intense positive staining for ki67 in both methods B and C, and also a patch positive stromal cells staining for Ki67. Expression of hsp70 was not increased after cryopreservation. Conclusions Cryopreservation using quartz vials led to larger numbers of good follicles while maintaining consistent preservation for stromal cells and vessels.